Pemphigus erythematosus relapse associated with atorvastatin intake - Lo Schiavo A; Puca RV; Romano F; Cozzi R (Dove Medical Press, 2014)
Ada Lo Schiavo,1 Rosa Valentina Puca,1 Francesca Romano,1 Roberto Cozzi2 1Department of Dermatology, Second University of Naples, Naples, Italy; 2Department of Dermatology, AORN "A Cardarelli", Naples, Italy Abstract: Statins, also known as 3-hydroxy-3-methylglutaril-CoA reductase inhibitors, are well-tolerated drugs used for prevention of atherosclerosis and cardiovascular events. Although they are generally considered safe, some serious adverse effects, such as myositis, myopathy, and rhabdomyolysis can rarely occur. Furthermore, recent data from long-term follow-up on patients who have been taking statins for a long period of time suggest that prolonged exposure to statins may trigger autoimmune reactions. The exact mechanism of statin-induced autoimmune reactions is unclear. Statins, as proapoptotic agents, release nuclear antigen into the circulation and may induce the production of pathogenic autoantibodies. Herein we report the case of a 70 year-old man who developed a relapse of pemphigus erythematosus, a syndrome with features of both lupus erythematosus and pemphigus, after atorvastatin intake. Keywords: pemphigus erythematosus, autoimmune disease, treatment, pathogenesis, statins